Pooled genome wide association detects association upstream of FCRL3 with Graves' disease. (December 2016) - Khong, Jwu; Burdon, Kathryn; Lu, Yi; Laurie, Kate; Leonardos, Lefta; Baird, Paul; Sahebjada, Srujana; Walsh, John; Gajdatsy, Adam; Ebeling, Peter; Hamblin, Peter; Wong, Rosemary; et al.
Abstract Background Graves' disease is an autoimmune thyroid disease of complex inheritance. Multiple genetic susceptibility loci are thought to be involved in Graves' disease and it is therefore likely that these can be identified by genome wide association studies. This study aimed to determine if a genome wide association study, using a pooling methodology, could detect genomic loci associated with Graves' disease. Results Nineteen of the top ranking single nucleotide polymorphisms including HLA-DQA1 and C6orf10, were clustered within the Major Histo-compatibility Complex region on chromosome 6p21, with rs1613056 reaching genome wide significance (p = 5 × 10−8 ). Technical validation of top ranking non-Major Histo-compatablity complex single nucleotide polymorphisms with individual genotyping in the discovery cohort revealed four single nucleotide polymorphisms withp ≤ 10−4 . Rs17676303 on chromosome 1q23.1, located upstream ofFCRL3, showed evidence of association with Graves' disease across the discovery, replication and combined cohorts. A second single nucleotide polymorphism rs9644119 downstream ofDPYSL2 showed some evidence of association supported by finding in the replication cohort that warrants further study. Conclusions Pooled genome wide association study identified a genetic variant upstream ofFCRL3 as a susceptibility locus for Graves' disease in addition to those identified in the Major Histo-compatibility Complex. A second locus downstream ofDPYSL2 is potentially a novel genetic variant in Graves' disease that requires further confirmation.